Securitization and credit quality - Alper Kara; David Marqués-Ibá\~nez; Steven Ongena (European Central Bank (ECB), 2017)
Banks are usually better informed on the loans they originate than other financial intermediaries. As a result, securitized loans might be of lower credit quality than otherwise similar non-securitized loans. We assess the effect of securitization activity on loans' relative credit quality employing a uniquely detailed dataset from the euro-denominated syndicated loan market. We find that, at issuance, banks do not seem to select and securitize loans of lower credit quality. Following securitization, however, the credit quality of borrowers whose loans are securitized deteriorates by more than those in the control group. We find tentative evidence suggesting that poorer performance by securitized loans might be linked to banks' reduced monitoring incentives. From our findings it follows that current iniciatives on risk retention by the originator, and more detailed loan-by-loan information on loan credit quality would be useful to reap out the benefits of securitization.
Keywords: G21; G28; 330; credit risk; European market; securitization